The effect of service quality and management style towards folder management and registration service on patients loyalty in Medical Records Unit Hospital Universiti Sains Malaysia (HUSM) / Nur Amaleena Radzali - Radzali, Nur Amaleena (2011)
A cross sectional study was conducted on the effect of service quality and management style towards folder management and registration service on patients loyalty in Medical Records Unit, Hospital Universiti Sains Malaysia (HUSM) , with the aim to determining the relationship and the effect of service quality and management style towards folder management and registration services on patients’ loyalty. Using a structured questionnaire, data were derived from 150 patients using simple random sampling. Descriptive statistics were used to describe satisfaction level and independent variable while the relationships between these factors were determined by estimates structural equation models (SEM). In this study, there are two independent construct namely service quality and management style. The study also has an intervening (mediating) construct namely patients’ satisfaction, and their intended dependent construct namely patients’ loyalty. The result supported that service quality of folder management and registration provided by Medical Records Unit has a significant and direct influence on patients’ satisfaction. The patients’ satisfaction also has a significant influence on patients’ loyalty. Strategies emphasizing improving the image of the Medical Records Unit should be continuously implemented while the service quality for the patients should be improved. Patients’ satisfaction surveys can be conducted in each unit to get the real picture for future strategies